On a Regularization Method for Solutions of a Certain Linear Ill-Posed Problem - Borisova, E. A. (Journal of mathematical sciences (New York, N.Y.), 2020)
An effective and easy regularization method for solutions of a linear ill-posed problem (namely, a Fredholm equation of the first kind) is proposed. Keywords and phrases: linear ill-posed problem, Fredholm equations, regularization of solutions. AMS Subject Classification: 47S99